2012
DOI: 10.1136/heartjnl-2011-300862
|View full text |Cite
|
Sign up to set email alerts
|

Translational phases of evidence in a prognostic biomarker: a systematic review and meta-analysis of natriuretic peptides and the prognosis of stable coronary disease

Abstract: The unbiased strength of association of NP with prognosis in stable coronary disease is unclear, and there is a lack of reports of clinically useful measures of prediction and discrimination or studies relating NP levels to clinical decision making. The available literature is confined to early phases and is of limited clinical usefulness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
0
4
0
2
Order By: Relevance
“…в web-приложе-нии) [70][71][72]. Магнитно-резонансную томография (МРТ) сер-дца также можно использовать для выявления струк-турных нарушений сердца и оценки функции желу-дочков [87].…”
Section: неинвазивные методы исследования сердцаunclassified
“…в web-приложе-нии) [70][71][72]. Магнитно-резонансную томография (МРТ) сер-дца также можно использовать для выявления струк-турных нарушений сердца и оценки функции желу-дочков [87].…”
Section: неинвазивные методы исследования сердцаunclassified
“…NIHR Journals Library www.journalslibrary.nihr.ac.uk Based on our published findings (Sutaria et al 511 ), the evidence update recommended extending existing systematic reviews continued DOI: 10.3310/pgfar05040 PROGRAMME GRANTS FOR APPLIED RESEARCH 2017 VOL. 5 NO.…”
Section: Conclusion and Implications For Clinical Practice And Furthmentioning
confidence: 99%
“…74 The same authors were equally critical of 19 BNP studies in patients with stable coronary disease, reporting that clinically useful measures of prediction and discrimination were generally unavailable, and concluding that the unbiased strength of association of BNP with prognosis in stable coronary disease is unclear. 75 The availability of highsensitivity assays has seen renewed interest in troponins as markers of risk in stable coronary disease, a US study of 984 patients in the Heart and Soul Study reporting that each doubling in hs-cTnT level is associated with a 37% higher rate of cardiovascular events. 76 Meanwhile the PEACE investigators have reported that among 3623 patients with stable coronary artery disease, hs-cTNI is independently associated with cardiovascular death or heart failure (HR 1.88 (1.33 to 2.66; p<0.001)), the association with non-fatal myocardial infarction being weaker (1.03 to 2.01; p=0.031).…”
Section: Prognostic Biomarkers In Stable Cadmentioning
confidence: 99%